TRADISI TUJUH BULANAN DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM ADAT ( Studi Kasus Di Desa Pohsangit Lor Kecamatan Wonomerto Kabupaten Probolinggo ) - Samsul Hadi; Moh. Lubsi Tuqo Romadhan; Imanudin Abil Fida (Fakultas Hukum Universitas Islam Syekh Yusuf, 2023)
The research conducted by the author is to find out the law of carrying out the Seven Monthly Bathing Tradition according to the views of Islamic law and customary law in Pohsangit Lor Village, Wonomerto District, Probolinggo Regency. This type of field research is the type of research that the author does accompanied by the use of descriptive qualitative research methods with a Phenomenological approach. Because this research leads to the form of phenomena that exist in society, the results of this research will be in the form of descriptive written or spoken words from living people and behavior available in various ways to interpret experiences through interactions with others. The results of the data obtained by the author are sourced from books, articles, journals and from the results of interviews that the author has conducted including with local community leaders, one of the elders in the village, traditional birth attendants and local residents. The results of the study state that the implementation of the Seven Monthly Bathing Tradition does not contain elements of shirk in it because the ceremony carried out today has occurred religious acculturation so that it contains many values of benefit for people who carry it out. Therefore, some scholars made a fatwa that the tradition is permissible, meaning that it is permissible if the community wants to carry it out but there is no obligation in it. Meanwhile, according to customary law, the implementation of the Seven Monthly Bathing Tradition has a mandatory nature in it because it is to maintain the preservation of customs and also pamali according to one of the elders there if they leave the tradition. Keywords: Seven Monthly Bathing Tradition, Islamic Law, Customary Law.